Long-Term Effects of Age Discrimination on Mental Health: The Role of Perceived Financial Strain. (14th March 2017) - Shippee, Tetyana P; Wilkinson, Lindsay R; Schafer, Markus H; Shippee, Nathan D
Abstract: Objectives: This study examines the role of work-related perceived age discrimination on women's mental health over the life course and tests whether financial strain mediates this relationship. Methods: Using the National Longitudinal Survey of Mature Women (1967–2003), we employ nested growth curve models to evaluate whether perceived age discrimination at work influences women's depressive symptoms and life satisfaction and whether perceived financial strain mediates this relationship. Results: Women who experienced age discrimination had greater overall depressive symptoms but not after controlling for financial strain. We found evidence that age discrimination affected financial strain, which, in turn, increased women's depressive symptoms. Women who reported age discrimination had lower odds of being in higher categories of overall life satisfaction; financial strain partially mediated the relationship but age discrimination remained a significant predictor. Discussion: Despite legal protection, age discrimination at work is frequent and has significant effects on women's mental health over the life course. Financial strain partially mediates this relationship, pointing to financial implications of perceived age discrimination for women and their families. Our findings have important policy and workplace implications, calling attention to ageism as a potent stressor for working women's mental health beyond those tied to sex or race.